Alternativas para auto-suficiência na produção de tomate, visando ao abastecimento da região metropolitana de Salvador, Bahia - Lima dos Santos, Lodisvaldo; Martins Rezende, Alberto; Paniago, Euter; do Nascimento Santos, Heleno (Revista Ceres, 2025)
The Metropolitan Region of Salvador, Bahia, showed an increase of 26.58% in tomato imports during the period of 1973/78. Since regional production increased by only 9.08% during the same period, consumption was heavily dependent upon imports from other states.